Skin Aging-Dependent Activation of the PI3K Signaling Pathway via Downregulation of PTEN Increases Intracellular ROS in Human Dermal Fibroblasts. (27th November 2016) - Noh, Eun-Mi; Park, Jinny; Song, Hwa-Ryung; Kim, Jeong-Mi; Lee, Minok; Song, Hyun-Kyung; Hong, On-Yu; Whang, Pyoung H.; Han, Myung-Kwan; Kwon, Kang-Beom; Kim, Jong-Suk; Lee, Young-Rae
Abstract : Reactive oxygen species (ROS) play a major role in both chronological aging and photoaging. ROS induce skin aging through their damaging effect on cellular constituents. However, the origins of ROS have not been fully elucidated. We investigated that ROS generation of replicative senescent fibroblasts is generated by the modulation of phosphatidylinositol 3, 4, 5-triphosphate (PIP3) metabolism. Reduction of the PTEN protein, which dephosphorylates PIP3, was responsible for maintaining a high level of PIP3 in replicative cells and consequently mediated the activation of the phosphatidylinositol-3-OH kinase (PI3K)/Akt pathway. Increased ROS production was blocked by inhibition of PI3K or protein kinase C (PKC) or by NADPH oxidase activating in replicative senescent cells. These data indicate that the signal pathway to ROS generation in replicative aged skin cells can be stimulated by reduced PTEN level. Our results provide new insights into skin aging-associated modification of the PI3K/NADPH oxidase signaling pathway and its relationship with a skin aging-dependent increase of ROS in human dermal fibroblasts.